A low capacitance single-phase AC-DC converter with inherent power ripple decoupling - Gottardo, Davide; De Lillo, Liliana; Empringham, Lee; Costabeber, Alessando (2016)
This paper proposes a new single-phase AC-DC conversion topology with inherent power ripple decoupling, based on the combination of a PWM H-bridge inverter, an AC side LC filter and a ZVS line commutated H-bridge. A capacitor on the AC side is used as power decoupling element. By appropriate selection of the capacitor voltage, the power ripple at twice the AC frequency can be cancelled from the DC side instantaneous power, achieving negligible DC voltage ripple using a smaller total capacitance compared to traditional solutions. Recently, several solutions using the concept of Ripple-Port have been proposed that reduce the overall capacitance. However, they usually need at least a dedicated PWM half-bridge leg, adding switching loss, and a separate LC tank. Instead, the proposed topology integrates the ripple compensation in the AC/DC conversion stage, exploiting the AC filter and minimising additional loss thanks to the ZVS of the additional H-bridge. The concept of the steady state operation of the proposed converter is described analytically and validated in simulation using MATLAB Simulink and PLECS. This work is being developed at University of Nottingham within the framework of project SENSIBLE.